PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H. (The Accounting Review, 1958)
The article presents details of problems prepared by the board of examiners of the American Institute of Certified Public Accountants and presented as the second half of the chartered public accountants examination in accounting practice in May 1958. The candidates were required to solve problems. The total weight assigned to this section of the examination was 50 points and the examiners point out that the suggested time allowances given below are approximately proportional to the point value of the various problems. From the following information set forth below one has to prepare a Federal income tax return for the calendar year 1957. Solution should show in schedule form all items going into the computation of the net taxable income, the computation of the tax and the final balance payable or overpayment of tax. Set up in good form any supporting computations needed in preparation of the return.